1)x²-3x+2=0
D=b²-4ac=(-3)²-4*1*2=9-8=1
x1=-b+√D/2a=3+1/2=2
x2=-b-√D/2a=3-1/2=1
ответ:2;1
2)x²-8x-20=0
D=b²-4ac=(-8)²-4*1*(-20)=64+80=144=12²
x1=-b+√D/2a=8+12/2=10
x2=-b-√D/2a=8-12/2=-2
ответ:10;-2
3)4z²+z-3=0
D=b²-4ac=1²-4*4*(-3)=1+48=49=7²
x1=-b+√D/2a=-1+7/8=0,75
x2=-b-√D/2a=-1-7/8=-1
ответ:0,75;-1
4)3y²-2y-8=0
D=b²-4ac=(-2)²-4*3*(-8)=4+96=100=10²
x1=-b+√D/2a=2+10/6=2
x2=-b-√D/2a=2-10/6=1,3
ответ:2;1,3
5)0,25x²-2x+3=0
D=b²-4ac=(-2)²-4*0,25*3=4-3=1
x1=-b+√D/2a=2+1/0,5=6
x2=-b-√D/2a=2-1/0,5=2
ответ:6;2
6)2z²-3z+0,75=0
D=b²-4ac=(-3)²-4*2*0,75=9-6=3
x1=-b+√D/2a=3+√3/4=1,1
x2=-b-√D/2a=3-√3/4=0,3
ответ:1,1;0,3
Объяснение:
Капец руки устали можешь мой ответ сделать лучшим. УДАЧИ
преобразуем неравенство
4*9/(3¹⁰/ˣ)-91/(3⁵/ˣ*4⁵/ˣ)+3*16/(4¹⁰/ˣ)≥0
умножим на 3¹⁰/ˣ, получим
36-91*(34/)⁵/ˣ+48*(3/4)¹⁰/ˣ, сделаем замену у=(3/4)⁵/ˣ>0,
36-91у+48у²≥0
36-91у+48у²=0; у=(91±√(8281-6912))/96; у=(91±37)/96; у=54/96=9/16=(3/4)²;
у=128/96=4/3=(3/4)⁻¹;
(у-(3/4)²)(у-(3/4)⁻¹)≥0
9/164/3
+ - +
а) (3/4)⁵/ˣ≤(3/4)²⇒5/х≥2; (5-2х)/х≥0 ; х=0; х=2.5;
02.5
- + -
х∈(0;2.5]
б) (3/4)⁵/ˣ≥(3/4)⁻¹; 5/х≤-1; (5+х)/х≤0; х=0; х=-5
-50
+ - +
х∈[-5;0)
ответ х∈[-5;0)∪(0;2.5]